2014
DOI: 10.1038/nnano.2014.6
|View full text |Cite
|
Sign up to set email alerts
|

A pomegranate-inspired nanoscale design for large-volume-change lithium battery anodes

Abstract: Silicon is an attractive material for anodes in energy storage devices, because it has ten times the theoretical capacity of its state-of-the-art carbonaceous counterpart. Silicon anodes can be used both in traditional lithium-ion batteries and in more recent Li-O2 and Li-S batteries as a replacement for the dendrite-forming lithium metal anodes. The main challenges associated with silicon anodes are structural degradation and instability of the solid-electrolyte interphase caused by the large volume change (∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
1,768
6
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,248 publications
(1,809 citation statements)
references
References 33 publications
26
1,768
6
9
Order By: Relevance
“…Yolk–shell architectures with inner buffering voids can provide reserved space to hold the expansion of active materials without destroying the protective sheaths, and the inner space is also beneficial to the rapid permeation of electrolyte 135, 136, 137, 138. Lee et al139 synthesized Sn/C york–shell nanospheres with Sn particles encapsulated in hollow spherical carbon shells through a soft template method ( Figure 13 a).…”
Section: Structure Design Of Sn‐based Anode Materialsmentioning
confidence: 99%
“…Yolk–shell architectures with inner buffering voids can provide reserved space to hold the expansion of active materials without destroying the protective sheaths, and the inner space is also beneficial to the rapid permeation of electrolyte 135, 136, 137, 138. Lee et al139 synthesized Sn/C york–shell nanospheres with Sn particles encapsulated in hollow spherical carbon shells through a soft template method ( Figure 13 a).…”
Section: Structure Design Of Sn‐based Anode Materialsmentioning
confidence: 99%
“…Compared with the insertion‐host electrode materials (carbon,16 oxide,16 and silicon16, 17 etc. ), there is no host for lithium metal anode during lithium ion plating, rendering the uncontrollable growth of dendrites.…”
Section: Introductionmentioning
confidence: 99%
“…Further, by utilizing in situ transmission electron microscopy (TEM), the effect of void space on the stability of structure, SEI thickness and performance was observed, and it is found that if the space is not enough for volume expansion then it causes structural disintegration (Figure 6). 52 Further, the use of self‐healing materials is another way to control the volume changes of anode materials, like self‐healing polymer was established to control the structural damages of silicon‐based electrode. Self‐healing polymer recover the cracks or other damages in structure during conversion reaction with Li + 84.…”
Section: Advanced Electrode Nanostructures For Lithium‐based Batteriesmentioning
confidence: 99%